IMPLEMENTATION OF CASE-BASED LEARNING TO IMPROVE STUDENTS' HIGHER-ORDER THINKING SKILLS (HOTS) AT SMAN 1 PARIANGAN - Fitri Nurul Deswita; Nofrion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low student motivation in learning, minimal student understanding of HOTS questions and lack of student learning outcomes for learning geography. Geography learning tends to be boring and meaningless, so learning objectives are not achieved. The weakness in geography learning is inadequate and monotonous learning models. Lecture-based learning models are often said to be less effective in geography learning. The study aimed to determine students' HOTS abilities after applying the case-based learning model to geography subjects at SMAN 1 Pariangan. Quantitative research type using experimental methods—Pre-test - Post-test control group design research design. The research population was all students of class XI geography Phase F SMAN 1 Pariangan 2024/2025 with 127 students. The research sample was class XI Geography 2 and class XI Geography 3 at SMAN 1 Pariangan. The sampling technique was purposive sampling. The sample in this study selected two classes, of which 1 class was used as an experimental class, namely XI Geo two and XI Geo three as the control group Data collection techniques were observation, documentation and testing. The research instrument is an objective test question sheet (case study) with assessment according to the criteria of the higher order thinking skills (HOTS) category such as analyzing, evaluating, creating, thinking critically and solving problems.The data obtained from this study were analyzed with the help of IBM SPSS 30 for the T and N-gain tests. The results of this study obtained a Pre-test Experiment score of 51.17, Post-Test results of 82.77, while the control class had a Pre-Test score of 49.29 and a Post-test of 69.97. There was a significant increase in the Pre-Test and Post-Test of the Experimental Class. This shows that the application of Case Based Learning has a positive effect on improving students' high-level thinking skills (HOTS) in geography subjects at SMAN 1 Pariangan, which can be seen from the learning outcomes and learning activities of students.Keywords: Case Based Learning, Higher Order Thinking Skills (HOTS),Environmental Problems Material,Quality Education, Geografi Learning.